2018
DOI: 10.1111/imcb.12028
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic control of dendritic cell numbers and differentiation

Abstract: Dendritic cells (DCs) are a diverse family of cells that play a crucial role in linking our innate and adaptive immune system to initiate adequate T-cell responses. They respond to pathogens by triggering the appropriate adaptive immune response that is required to clear invaders while balancing the need to limit tissue damage as a result of inflammation. Perturbation in DC regulation results in abnormal T-cell homeostasis, leading to development of autoimmune diseases and aberrant responses to pathogens. In r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 70 publications
0
39
0
1
Order By: Relevance
“…The identification of molecular mechanisms responsible for homeostatic myelopoiesis has been a long-standing task (for review, see Dress et al, 2018;Ginhoux and Guilliams, 2016;Schlitzer et al, 2015a). The recent introduction of single cell resolution technologies, particularly single cell transcriptomics, mass cytometry, and high-dimensional flow cytometry extend our knowledge considerably illustrating an unprecedented heterogeneity within the myeloid progenitor repertoire in both functional and transcriptomic phenotypes.…”
Section: Homeostatic Modulators Of Myelopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of molecular mechanisms responsible for homeostatic myelopoiesis has been a long-standing task (for review, see Dress et al, 2018;Ginhoux and Guilliams, 2016;Schlitzer et al, 2015a). The recent introduction of single cell resolution technologies, particularly single cell transcriptomics, mass cytometry, and high-dimensional flow cytometry extend our knowledge considerably illustrating an unprecedented heterogeneity within the myeloid progenitor repertoire in both functional and transcriptomic phenotypes.…”
Section: Homeostatic Modulators Of Myelopoiesismentioning
confidence: 99%
“…During homeostasis, hundreds of millions of neutrophils and monocytes are generated via myelopoiesis; however, there is still only limited understanding of the many factors involved in regulating this enormous cellular output (Furze and Rankin, 2008;Manz and Boettcher, 2014). Whereas elevated white blood cell counts, including monocytosis and neutrophilia, are commonly used in the clinic as surrogates for the presence of infection and/or inflammation, the molecular mechanisms that modulate myelopoiesis under diverse pathophysiological conditions are only beginning to be understood (Boettcher and Manz, 2016;Dress et al, 2018;Ginhoux and Guilliams, 2016;Manz and Boettcher, 2014;Medzhitov, 2008;Netea et al, 2016;Schlitzer et al, 2015a). Originally termed emergency granulopoiesis and demand-adapted myelopoiesis (Boettcher and Manz, 2016;Manz and Boettcher, 2014), we now also know that myelopoiesis is involved in innate immune memory or trained immunity (Mitroulis et al, 2018a; Mitroulis et al, 2018b;Netea et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This pool is composed of monocytes, macrophages, and dendritic cells (DCs). Ontogeny, heterogeneity and specific functions of these cells have been extensively described in various recent reviews (e.g., ).…”
Section: Introductionmentioning
confidence: 99%
“…Major DC subsets are classified into cDCs and pDCs, even though recent studies have shown increasingly complex classification of DC subpopulations and progenitors during ontogeny (Dress et al, 2018). Signalling mechanisms how TGF-β regulates the differentiation of DC subsets in the steady state remained largely unknown, although its importance in immunogenic and tolerogenic functions of the differentiated DCs have been appreciated (Seeger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A web of cytokine signalling pathways and transcription programs control development of DC subsets from distinct hematopoietic lineages (Lin) (Belz et al, 2012;Dress RJ et al, 2018;Merad et al, 2013;Miller et al, 2012;Murphy et al, 2016). Several cytokine receptors such as Fms-related tyrosine kinase 3 (FLT3; CD135), c-KIT (CD117) and macrophage colonystimulating factor receptor (M-CSFR; CD115) are the markers to distinguish Lin -DC progenitors in mouse bone marrow (BM).…”
Section: Introductionmentioning
confidence: 99%